Uji Efektivitas Teknik Ekstraksi dan Dry Heat Treatment terhadap Kesehatan Bibit Cabai Rawit (Capsicum frutescensL.) - I PUTU RINATA ASTAWA; I GUSTI NGURAH RAKA; NI NYOMAN ARI MAYADEWI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2016)
ABSTRACT Effectiveness of Technique Extraction Test and Dry Heat Treatment to Seed Health of Chili Pepper (Capsicum frutescens L.). Chili (Capsicum frutescens L.) is one of the horticultural crops of the Solanaceae family that has a high economic value. Seed healty problems is one of the chili pepperproduction constraints. Chili seeds used by farmers mostly contaminated by seed-borne diseases such as viruses. This study aims to determine the effectiveness of seed extraction techniques and Dry Heat Treatment (DHT) in producing healthy red pepper seeds in a seed source trials of healthy plants and diseased plants. The design used in this research is completely randomized design (CRD) with 2 factors. The first factor was the extraction technique which consisted of three levels ie extraction technique using 2% HCl, extraction techniques using quicklime and extraction techniques using water. The second factor was DHT with 2 levels ie DHT and without DHT (NDHT). The results of this research showed that DHT treatment was effective in producing healthy chili pepper seedlings with healtinese 100%, while seed extraction techniques has not been effective to produce healthy red pepper seeds with a percentage of less than 90%. Interaction between extraction techniques and DHT on trial seed originating from sick plants showed real influence. Keywords: chili pepper, extraction techniques, Dry Heat Treatment, healthy seed